Relationships between a Dissociative Subtype of PTSD and Clinical Characteristics in Patients with Substance Use Disorders. Issue 3 (27th May 2017) - Mergler, Michaela; Driessen, Martin; Lüdecke, Christel; Ohlmeier, Martin; Chodzinski, Claudia; Weirich, Steffen; Schläfke, Detlef; Wedekind, Dirk; Havemann-Reinecke, Ursula; Renner, Walter; Schäfer, Ingo; ,
ABSTRACT: The increasing support for a dissociative subtype of post-traumatic stress disorder (PTSD-D) has led to its inclusion in DSM-5. We examined relationships between PTSD-D and relevant variables in patients with substance use disorders (SUD). The sample comprised N = 459 patients with SUD. The International Diagnostic Checklist and the Posttraumatic Diagnostic Scale were used to diagnose PTSD. In addition, participants completed the Childhood Trauma Questionnaire and the Dissociative Experiences Scale. The course of SUD was assessed by means of the European Addiction Severity Index. One-fourth of participants fulfilled a diagnosis of PTSD (25.3%). Patients with PTSD-D ( N = 32, 27.6% of all patients with PTSD) reported significantly more current depressive symptoms, more current suicidal thoughts, more lifetime anxiety/tension, and more suicide attempts. The PTSD-D group also showed a significantly higher need for treatment due to drug problems, higher current use of opiates/analgesics, and a higher number of lifetime drug overdoses. In a regression model, symptoms of depression in the last month and lifetime suicide attempts significantly predicted PTSD-D. These findings suggest that PTSD-D is related to additional psychopathology and to a more severe course of substance-related problems in patients with SUD, indicating that this group also has additional treatment needs.